A polyolefin-based extruded resin foam having a sliced surface having antiviral properties and a method for producing said polyolefin-based extruded resin foam.
The extruded polyolefin resin foam with a sliced surface and inorganic antiviral agents effectively addresses the challenge of insufficient antiviral performance in conventional foams, achieving high virus reduction rates and stability across various expansion ratios.
Patent Information
- Application Number
- JP2020172526
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-13
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2040-10-13
AI Technical Summary
Conventional extruded polyolefin resin foams do not adequately exhibit antiviral effects, particularly for non-enveloped viruses, as antiviral agents are difficult to expose and maintain effectiveness on the surface due to the non-foamed skin layer.
The development of an extruded polyolefin resin foam with a sliced surface that exposes the cell walls of the foamed layer, incorporating inorganic antiviral agents such as zirconium phosphate with silver or silver compounds, phosphate compounds with calcium and zinc, zeolite with silver and copper, and silver-supported montmorinite, along with a surfactant, to enhance antiviral properties.
The sliced surface design and use of inorganic antiviral agents significantly increase the antiviral efficacy, achieving a virus reduction rate exceeding 99% and an activity value above 2.0, even at high expansion ratios of 20 to 40 times, while maintaining thermal stability and foam stability.
Smart Images

Figure 0007608107000001 
Figure 0007608107000002 
Figure 0007608107000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an extruded polyolefin resin foam having an antiviral sliced surface and a method for producing the extruded polyolefin resin foam. The present invention further relates to an extruded polyolefin resin foam having sufficient antiviral effect not only in the case of a low expansion ratio but also in the case of a high expansion ratio. [Background technology]
[0002] Unlike bacteria, viruses do not have cell membranes or ribosomes, and are composed of a protein membrane called an envelope and either DNA or RNA. However, since viruses do not have an envelope, they are particles with a shell called a capsid, and therefore cannot replicate themselves through their own energy metabolism like bacteria.
[0003] Therefore, viruses grow by parasitizing animals, plants, or bacteria. Viruses can be classified into membrane-bound viruses, which have a membrane called an envelope, and membrane-less viruses, and the effects of antiviral agents on viruses can be considered as follows, due to the structural differences between bacteria and viruses as described above.
[0004] In the case of enveloped viruses, the envelope is often made of fat or other materials, so organic surfactants may be effective, but in the case of non-membrane viruses, organic surfactants may not necessarily be effective.
[0005] Specific examples of organic surfactants having antiviral properties include linear alkydobenzenesulfonic acid, alkyl glycosides, alkylamine oxides, benzalkonium chloride, benzethonium chloride, dialkyldimethylammonium chloride, polyoxyalkyl ethers, etc. In addition, organic antiviral agents such as organic surfactants have problems with thermal stability.
[0006] On the other hand, in the case of heavy metal antiviral agents, the following mechanisms are thought to be responsible: For example, the inhibitory effects of heavy metals such as Ag and Cu as antiviral agents are thought to be 1) inhibition of membrane fusion between cells and viruses, in which heavy metal complexes and heavy metal ions bind to the envelope and inhibit membrane fusion with cells, thereby inhibiting binding to the host, and 2) inhibition of replication system enzymes, in other words, heavy metal complexes and heavy metal ions inhibit replication system enzymes.
[0007] Furthermore, Ag ions and Cu ions generate singlet oxygen, which has higher energy than normal triplet oxygen, i.e., they generate so-called active oxygen. The singlet oxygen generated here reacts with water to generate hydroxyl radicals (·OH), which are thought to have an antiviral effect.
[0008] Since antibacterial agents and antiviral agents are closely related, for reference, the inhibitory effects of antibacterial agents are described in Non-Patent Document 1. In summary, Non-Patent Document 1 describes that the mechanism of action of antibacterial agents may include inhibition of cell wall synthesis, inhibition of cell wall synthesis, inhibition of protein synthesis associated with inhibition of translation and transcription of genetic material, inhibition of nucleic acid synthesis, etc.
[0009] Specifically, Non-Patent Document 1 describes that, first, inhibition of cell wall synthesis causes the cell to collapse, as the cell wall plays a role in maintaining the cell's shape and internal osmotic pressure, and that inhibition of cell wall synthesis leads to the collapse of the cell; second, inhibition of cell membrane function causes dysfunction of the cell membrane, which has selective permeability and functions to transport components inside the cell and regulate the components inside the cell, but inhibition of cell membrane function causes macromolecules and ions inside the cell to leak out, resulting in cell damage and cell death.
[0010] Next, Non-Patent Document 1 states that, thirdly, there is the inhibition of protein synthesis accompanying the inhibition of the translation and transcription of genetic material; when an antibacterial agent adheres to bacterial ribosomes, proteins that do not have translation or transcription functions are synthesized, or the ribosomes are destroyed, making protein synthesis impossible and preventing cell growth; and, fourthly, there is the inhibition of nucleic acid synthesis; when an antibacterial agent binds to DNA to form a complex, it blocks the inhibition of mRNA formation and inhibits bacterial growth.
[0011] As mentioned above, viruses can be classified into those that are enveloped in a membrane containing lipids, called an envelope, and those that do not. In the case of membrane-containing viruses, the envelope is mostly composed of lipids, so they can be easily destroyed by treatment with organic antiviral agents such as ethanol, organic solvents, and soap.
[0012] For this reason, while enveloped viruses are generally easy to inactivate, non-enveloped capsid viruses are said to be highly resistant to the above-mentioned treatment agents, and it is believed that antiviral agents different from organic antiviral agents are necessary.
[0013] In the present invention ,main The study will focus on a polyolefin-based extruded resin foam having a sliced surface with antiviral properties, which uses an inorganic antiviral agent using a metal ion as an antiviral agent, and a method for producing the polyolefin-based extruded resin foam.
[0014] Patent Document 1 discloses an invention relating to expandable resin particles containing an inorganic antibacterial agent having an average particle size of 0.1 to 2.0 μm. Patent Document 1 also describes an antibacterial synthetic resin foam molded product obtained by pre-expanding the antibacterial expandable microparticles and then subjecting them to secondary expansion molding.
[0015] Furthermore, the molded article of Patent Document 1 has the same antibacterial properties even on the sliced surface after secondary processing of the skin layer and the inside of the foam layer. It is described that the expandable microparticles contain 0.01 to 5.0 parts by mass of a metal ion antibacterial agent and 0.01 to 2.0 parts by weight of hardened oil per 100 parts by mass of the expandable microparticles, and that the metal ions are supported by zirconium phosphate. It is further described that it is desirable to contain a fatty acid ester.
[0016] Patent Document 2 describes a foamed sheet having at least one surface coated with an organic specific compound selected from the group consisting of palmityl diethanolamine, stearyl diethanolamine, glycerin monolaurate, and glycerin monocaprate in an amount of 0.002 to 0.05 (g / m 2 ) is laminated on an antibacterial thermoplastic resin foam sheet.
[0017] In addition, the film laminated on the foamed sheet in Patent Document 2 is laminated after foaming, and the foamed sheet has an expansion ratio of 2 times, a foam thickness of 1 mm, and the laminated film is a thin material with a thickness of about 30 to 40 μm, and is a biaxially oriented multilayer film.
[0018] Patent Document 3 relates to an antiviral agent, a resin composition, and an antiviral product, and describes an antiviral agent containing an inorganic solid acid having an acid site concentration of more than 0.005 mol / g, the inorganic solid acid containing silver, copper, or any one of these compounds in addition to an inorganic phosphate compound, an inorganic silicic acid compound, or an inorganic oxide, and a resin composition containing this antiviral agent. Furthermore, Patent Document 3 describes that the acid strength (pKa) of the acid site in the inorganic solid acid is preferably 3.3 or less.
[0019] Furthermore, in Patent Document 3, the antiviral agent is sprayed or painted onto textile products such as clothing, bedding, and masks, filters used in air purifiers and air conditioners, interior products such as curtains, carpets, and furniture, and automobile interior materials, or is spread onto the surface layers of building materials such as wallpaper and flooring materials, thereby imparting the effect of reducing viral activity.
[0020] Patent Document 4 describes an antimicrobial member in which a cured binder containing an antimicrobial component is fixed to a substrate surface, and the cured binder is formed on the substrate surface, and the substrate surface has a gloss level according to JIS Z8741 of 45% or more and less than 100%.
[0021] Furthermore, Patent Document 4 describes inorganic antimicrobial agents such as silver, copper, zinc, platinum, zinc compounds, silver compounds, copper compounds, metal oxide catalysts carrying metals or metal oxides, zeolites ion-exchanged with metal ions, and copper complexes.
[0022] Patent Document 4 describes an antimicrobial member in which the organic antimicrobial agent is at least one selected from the group consisting of antimicrobial resins, sulfonic acid surfactants, copper alkoxides, and bis-type quaternary ammonium salts, and Patent Document 4 describes that the binder cured material includes a binder cured material composed of an organic binder, an inorganic binder, and an organic-inorganic hybrid binder.
[0023] (Antibacterial zeolite + resin composition + silver, copper, etc.) Patent Document 5 describes the provision of an antibacterial zeolite that is unlikely to cause discoloration over time even when contained in a resin or the like, and an antibacterial zeolite containing the antibacterial zeolite, and further describes an antibacterial zeolite in which some or all of the ion-exchangeable ions in the zeolite are replaced with hydrogen ions and silver ions, and an antibacterial resin composition containing 0.05 to 80 mass % of the antibacterial zeolite.
[0024] Furthermore, Patent Document 5 describes a well-known antibacterial zeolite in which the ion-exchangeable metal ions of zeolite are replaced with antibacterial metal ions such as silver, copper, and zinc, and an antibacterial composition containing the same, and describes a technology in which the zeolite contains silver ions and ammonium ions to solve the problem of discoloration over time that occurs with antibacterial zeolite, for an antibacterial resin composition containing the antibacterial zeolite.
[0025] Patent Document 6 discloses a virus inactivation sheet capable of inactivating attached viruses, which is characterized by comprising a sheet body and monovalent copper compound microparticles and / or iodide microparticles held by the sheet body.
[0026] Patent Document 6 describes a virus inactivation sheet in which the monovalent copper compound microparticles are at least one selected from the group consisting of chlorides, acetates, sulfides, iodides, bromides, peroxides, oxides, and thiocyanides, and further describes a virus inactivation sheet in which the iodide microparticles contain a large number of iodide particles.
[0027] The inactivation sheet of Patent Document 6 describes that the monovalent copper compound microparticles and / or iodide microparticles are held on the sheet body via a group of other inorganic microparticles that are fixed to the sheet body by chemical bonds with silane monomers and / or polymers of silane monomers.
[0028] An antiviral agent was kneaded into the resin foam to impart antiviral properties, but because a non-foamed layer known as the skin layer exists on the surface of the foam, the antiviral agent particles are present in the non-foamed layer on the surface of the foaming agent and are therefore difficult to expose, making it impossible to obtain a sufficient antiviral effect.
[0029] Furthermore, in the case of Patent Document 1, expandable resin particles are used as a raw material, and hardened oil or fatty acid ester is used as a binder for applying and fixing an antibacterial agent to the expandable resin particles as a raw material for a foam, but the present invention is different in that no binder is required. Furthermore, since the antibacterial expandable microparticles are pre-expanded and then secondary expansion-molded to produce an antibacterial synthetic resin foam molded body, the molded body of Patent Document 1 is a secondary molded body made from antibacterial expandable microparticles as a raw material, and is not an extruded foam made by directly kneading an antiviral agent into a base resin and continuously molding it as in the present invention. Since the antibacterial layer is applied to the surface of the expandable resin particles by a binder, it is considered to be present inside the foam bubble walls that are fused together during foaming, whereas the present invention is based on a different technical idea from that of the present application, which targets the antiviral agent exposed on the bubble wall surface. Furthermore, the present invention does not have problems such as powder falling off and blocking from the expandable particles and pre-expanded particles of the antiviral agent, which are problems in Patent Document 1.
[0030] Patent Document 2 discloses an antibacterial thermoplastic resin foam sheet laminated with a film, but the foam itself is not given antibacterial or antiviral properties. The antiviral agent, resin composition, and antiviral product of Patent Document 3 do not impart antiviral activity to the sliced surface of the resin foam. Patent Document 4 discloses organic antiviral agents, inorganic antiviral agents, hybrid antiviral agents, and ion-exchanged zeolites as antiviral agents, but these do not impart antiviral properties to the sliced surface of the resin foam. Patent Document 5 discloses a composition containing antibacterial zeolite containing antibacterial metal ions such as silver, copper, and zinc, and Patent Document 6 describes a virus inactivation sheet containing monovalent copper compound particles or iodide particles, but none of them impart antiviral properties to the sliced surface of the resin foam. [Prior art documents] [Patent documents]
[0031] [Patent Document 1] Japanese Patent Application Publication No. 11-335481 [Patent Document 2] JP 2015-48391 A [Patent Document 3] International Publication No. 2017 / 150063 [Patent Document 4] JP 2020-083779 A [Patent Document 5] International Publication No. 2007 / 037195 [Patent Document 6] International Publication No. 2011 / 040048 [Non-patent literature]
[0032] [Non-Patent Document 1] Yasuhiro Iwasawa, "Interface Handbook," NTS Publishing, September 2001 Summary of the Invention [Problem to be solved by the invention]
[0033] As described above, there has been no sheet-shaped polyolefin-based extruded resin foam produced by extrusion foaming up to now that can fully exert antiviral effects. The present invention has been made in view of such facts, and aims to provide a polyolefin-based extruded resin foam having an antiviral agent-supported particle kneaded into the base resin of a foaming agent before molding, dispersed in the foam, and then slicing the foam to have the antiviral agent present on the sliced surface, thereby enabling the antiviral effect to be exerted, and to provide a polyolefin-based extruded resin foam having a sliced surface having antiviral properties, and a method for producing the polyolefin-based extruded resin foam. [Means for solving the problem]
[0034] Inorganic At least one surface of the polyolefin-based extruded resin foam containing an antiviral agent is a sliced surface in which cell walls constituting a foam layer are open, and the sliced surface is Inorganic Antiviral drugs emerge The foam has a closed cell structure with an expansion ratio of 20 to 40 times and an average cell diameter of 200 to 1500 μm. Polyolefin extruded resin foam And, The inorganic antiviral agent contained in the polyolefin-based extruded resin foam is any one of: (1) zirconium phosphate carrying silver or a silver compound by ion exchange; (2) a phosphate compound having a hydroxyapatite composition containing calcium and zinc carrying silver or silver ions by ion exchange; (3) zeolite carrying silver or copper by ion exchange; or (4) silver-carrying montmorillonite; The extruded polyolefin resin foam contains 1 to 8 parts by mass of at least one of the inorganic antiviral agents in total, and further contains 0.5 to 4 parts by mass of a surfactant, relative to 100 parts by mass of a polyolefin resin.
[0037] The polyolefin-based extruded resin foam is Inorganic In addition to antiviral agents, antioxidants For 100 parts by weight of polyolefin resin The antioxidant may be contained in an amount of 0.05 to 1 part by mass. The content of the antioxidant is preferably 0.1 to 0.8 parts by mass.
[0038] The sliced surface of the polyolefin-based extruded resin foam is ,table The extruded polyolefin resin foam is characterized in that the skin layer of the extruded polyolefin resin foam is removed, the center of the extruded polyolefin resin foam in the thickness direction is sliced straight, or the center of the extruded polyolefin resin foam in the thickness direction is profiled.
[0039] The polyolefin-based extruded resin foam The above On the opposite side of the sliced surface, another polyolefin-based extruded resin foam is but Paste Be The present invention relates to an extruded polyolefin resin foam, characterized in that the foam is laminated.
[0040] The base resin of the polyolefin-based extruded resin foam includes low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, very low-density polyethylene, polypropylene, polybutene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, and polypropylene, and the polyolefin-based extruded resin foam is characterized in that it is made of at least one of these or a mixture of two or more of these blended together.
[0041] The extruded polyolefin resin foam is characterized in that an uneven pattern is formed on the surface of the extruded polyolefin resin foam.
[0042] The polyolefin-based extruded resin foam is characterized in that it is used for a mat for an evacuation shelter.
[0043] Contains inorganic antiviral agents A method for producing an extruded polyolefin resin foam, comprising the steps of: The inorganic antiviral agent contained in the polyolefin-based extruded resin foam is any one of: (1) zirconium phosphate carrying silver or a silver compound by ion exchange; (2) a phosphate compound having a hydroxyapatite composition containing calcium and zinc carrying silver or silver ions by ion exchange; (3) zeolite carrying silver or copper by ion exchange; and (4) silver-carrying montmorillonite, The composition contains 1 to 8 parts by mass of at least one of the inorganic antiviral agents in total, and further contains 0.5 to 4 parts by mass of a surfactant, relative to 100 parts by mass of a polyolefin resin, The inorganic After the polyolefin-based extruded resin foam containing the antiviral agent is foamed at a predetermined ratio, the foam layer near the surface is cut to expose the openings where the cell walls of the foam layer are opened, or the foam layer is cut at the center in the thickness direction of the polyolefin-based extruded resin foam or at a position offset by a predetermined distance from the center in the thickness direction to open the cell walls of the foam layer, by slicing or profiling. The foam has a closed cell structure with an expansion ratio of 20 to 40 times and an average cell diameter of 200 to 1500 μm. A method for producing an extruded polyolefin resin foam. Here, the total content of the antiviral agent is preferably 1 to 6 parts by mass per 100 parts by mass of the polyethylene resin of the base material. Since the object of the present invention is to expose the foam layer of the extruded polyolefin resin foam, the antiviral agent used in the present invention is composed of an inorganic antiviral agent.
[0044] The method for producing an extruded polyolefin resin foam of the present invention may further include shaping the resin foam by further slicing at least a part of the sliced or profiled surface. The method for producing an extruded polyolefin resin foam of the present invention is characterized in that another extruded polyolefin resin foam is attached and laminated to the surface opposite to the sliced surface of the extruded polyolefin resin foam.
[0047] (Base resin for polyolefin-based extruded resin foam) Examples of base resins for the polyolefin-based extruded resin foam of the present invention include low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, very low-density polyethylene, polypropylene, polybutene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-methyl acrylate copolymer, and ethylene-ethyl acrylate copolymer. These can be used alone or as a mixture of two or more types blended together, with low-density polyethylene being preferred.
[0048] (Antiviral Agents) The antiviral agent in the present invention is an inorganic antiviral agent. Use a drug Inorganic antiviral agents are preferred from the viewpoint of thermal stability. Inorganic antiviral agents do not decompose even when exposed to high temperatures during kneading and molding in obtaining a polyolefin-based extruded resin foam, and can impart sufficient antiviral properties to the foam. Inorganic antiviral agents other than copper-based ones and silver-based antiviral agents are preferred from the viewpoint of suppressing the acceleration of resin deterioration. It is preferable to use a This is because heavy metals, especially copper, have the effect of accelerating the thermal degradation of polyolefin resins.
[0049] In particular, it is preferable to use the following antiviral agents: zirconium phosphate carrying silver or a silver compound by ion exchange, a phosphate compound having a hydroxyapatite composition containing calcium / zinc carrying silver or silver ions, zeolite carrying silver or copper by ion exchange, or silver-carrying montmorillonite carrying a metal-based antiviral agent carried on an inorganic compound.
[0050] If the content of the antiviral agent is too low, the antiviral properties are weak, and if it is too high, the generation of bubbles during foaming becomes unstable, which results in a foam with a high expansion ratio being difficult to obtain, the ends of the foam being easily burned, and the antiviral agent being easily aggregated, and the cost also increases. The content of the antiviral agent is preferably 1 to 8 parts by mass relative to 100 parts by mass of the polyolefin resin. Within this range, it is easy to achieve both antiviral properties and a good foam. It is more preferably 1 to 6 parts by mass.
[0051] (silver or silver compound ion-exchanged zirconium phosphate) Supports using compounds carrying silver, copper, zinc, or the like as antiviral agents include various inorganic solid acids, and particularly representative ones include those using zirconium phosphate, those using phosphate ceramics, those carrying the compound on glass, and those using magnesium aluminosilicate or clay minerals.
[0052] In the present invention, the content of zirconium phosphate carrying silver or a silver compound is set to 1 to 8 parts by mass, because a predetermined antiviral effect can be obtained even with a content of 8 parts by mass, and if the content is 8 parts by mass or more, the generation of bubbles becomes unstable and the dispersibility decreases, and the production cost of the resin foam increases. Considering the balance of these properties, the upper limit of the content of zirconium phosphate is preferably 6 parts by mass. Also, if the content is less than 1 part by mass, the antiviral effect is observed but is weak, so it is preferable to contain 1 part by mass or more. Therefore, the content of zirconium phosphate is preferably 1 to 6 parts by mass.
[0053] As an inorganic solid acid, a material containing at least one of silver, copper, and their compounds in addition to zirconium phosphate as an inorganic oxide can be used as an antiviral agent. Specifically, it is possible to use hexagonal zirconium phosphate, which is an inorganic ion exchanger, which supports silver ions by ion exchange.
[0054] Zirconium-centered oxygen octahedra and phosphorus-centered oxygen tetrahedra are linked three-dimensionally with oxygen sharing, and silver ions exist in the cavities of the framework. Here, for example, to obtain zirconium phosphate carrying silver, first, a zirconium oxychloride aqueous solution of a predetermined concentration is added to a phosphoric acid aqueous solution of a predetermined concentration, and the mixture is aged at 100°C for 12 hours, and then the resulting precipitate is washed with water and dried to recover zirconium phosphate.
[0055] Next, this zirconium phosphate precipitate was stirred in an aqueous silver nitrate solution at 100° C. for 2 hours. The precipitate obtained was then filtered, washed with water, dried and crushed to obtain an α-type zirconium phosphate powder containing a predetermined amount of white silver. In addition to silver nitrate, aqueous solutions of silver sulfate, silver perchlorate, silver acetate, diamine nitrate, diamine sulfate, etc. can be used.
[0056] In the present invention, a zirconium phosphate catalyst carrying silver or a silver compound is used. Antiviral The agent used was Toa Gosei's Novaron IV1000. The average particle size of Novaron IV1000 is 1 to 2 μm, and the weight of Ag supported on the zirconium phosphate is about 10% by weight of the weight of the zirconium phosphate.
[0057] (A phosphate compound containing calcium and zinc carrying silver or silver ions) Similarly, instead of zirconium phosphate, a compound in which silver or silver ions are supported on a phosphate compound in which calcium and zinc are combined may be used as the antiviral agent. The composition of this antiviral agent is a phosphate compound in which calcium and zinc are combined, and has a hydroxyapatite composition represented by the following formula (1). (1)Ag-CaαZnβAlγ(PO4)δ(OH)2
[0058] The phosphate compound having a hydroxyapatite composition carrying Ag is produced as follows. First, a crude reaction is carried out to synthesize a phosphate compound having a calcium and zinc complex using calcium hydroxide, zinc oxide, aluminum hydroxide, and phosphoric acid as raw materials. Next, silver nitrate is added and a mechanochemical reaction is carried out using a ball mill to carry out silver ions at the acid sites of the phosphate compound, after which the product is washed and filtered, and pulverized to obtain a fine powder of a specified size.
[0059] The amount of Ag supported by this material is 10% by weight of the phosphate compound. The average particle size of this material can be 1 μm or less. Here, the content of the phosphate compound complexed with calcium and zinc as an antiviral agent relative to 100 parts by mass of the base resin is 1 to 8 parts by mass, preferably 1 to 6 parts by mass. The reasons for specifying these numerical values are the same as those for zirconium phosphate.
[0060] (Zeolite carrying silver and copper by ion exchange) In the present invention, it is well known that ion-exchanged zeolites containing silver and copper have an antiviral effect. Therefore, the characteristics of ion-exchanged zeolites with antibacterial properties will be briefly reviewed. Zeolites used as antiviral agents are zeolites that are supported by ion exchange with antibacterial metals such as silver, copper, and zinc. Silver ions have the highest ion exchangeability among metal ions, and the oxidation-reduction potential of silver ions is +0.798 V (25°C) with respect to the standard potential, which is the highest among metals, making them highly reactive.
[0061] Zeolite is a type of aluminosilicate, and generally consists of aluminum, silicon, alkali metals, alkaline earth metals, and oxygen. The smallest unit that makes up zeolite is a SiO4 or AlO4 tetrahedron formed with oxygen at the vertices, which are bonded three-dimensionally to share oxygen atoms. In zeolite, the Al portion is electrically negatively charged, and alkali metals or alkaline earth metals are electrostatically bonded to this portion, making it stable.
[0062] Zeolite is characterized by having four main functions: adsorption function, molecular sieve function, catalytic function, and ion exchange function. The ion exchange function of zeolite is created by binding an equal amount of cations within the structure to neutralize the negative charges of the AlO4 tetrahedra within the zeolite structure.
[0063] The manufacturing method of zeolite, for example, A-type zeolite, is to first mix sodium aluminate solution and sodium silicate solution to precipitate amorphous aluminosilicate, then crystallize at 95℃ to make raw zeolite. Silver zeolite can be made by adding zeolite to silver nitrate solution and reacting it through ion exchange.
[0064] Here, in order to obtain silver ion-exchanged zeolite, silver sulfate, silver perchlorate, silver acetate, diamine silver nitrate, diamine silver sulfate, etc. can be used in place of silver nitrate. To obtain copper ion-exchanged zeolite, an aqueous solution of copper chloride, copper acetate or copper propionate can be used when the zeolite is contacted with an aqueous solution containing copper ions to exchange the cations contained in the zeolite crystals for copper ions. Similarly, to obtain zinc ion-exchanged zeolite, an aqueous solution of zinc acetate, zinc carbonate, zinc chloride or zinc oxide can be used. In the present invention, a zeolite in which silver ions and copper ions are substituted is used.
[0065] In the present invention, the antiviral agent contains 1 to 8 parts by mass of ion-exchanged zeolite relative to 100 parts by mass of the base resin. The amount of ion-exchanged zeolite can be 8 parts by mass or more, but a predetermined antiviral property can be obtained even with 8 parts by mass. If the amount is 8 parts by mass or more, crosslinking is inhibited, the generation of bubbles becomes unstable, and at the same time, the dispersibility is reduced, and the product cost of the resin foam increases. Therefore, the upper limit of the content of ion-exchanged zeolite is 8 parts by mass. Considering the balance of these properties, the upper limit of the content of zirconium phosphate is preferably 6 parts by mass. The reason why the lower limit is set to 1 part by mass is that if the content of ion-exchanged zeolite is less than this, the antiviral effect is recognized but is weak, so it is desirable to contain 1 part by mass or more. Therefore, the content of zeolite is preferably 1 to 6 parts by mass.
[0066] In the present invention, as a zeolite-based antibacterial agent containing silver and copper, ion-exchanged zeolite with the trade name Zeomic AC10D by Sinanen Zeomic is used. The average particle size of the zeolite is 2 to 3 μm. The amounts of Ag and Cu contained in the zeolite are 2.2% by weight for Ag and 3.6% by weight for Cu.
[0067] (Silver-loaded montmorillonite) Instead of zeolite, the antiviral agent may be supported on other mineral compounds. For example, there is smectite mineral. Smectite group minerals are flake-like particles that are usually several μm or less in size and have a strong anisotropy, and have a cation exchange capacity. Therefore, smectite group minerals can be used instead of zeolite.
[0068] Smectite group minerals have a layered structure of octahedra and tetrahedra, with the octahedra sharing their pieces to form two-dimensionally large octahedral layers, and the tetrahedra sandwiching two tetrahedral layers from above and below, giving them a two-dimensional spread. Representative examples of smectite group minerals include montmorillonite and the synthetic mineral saponite.
[0069] Here, the centers of each tetrahedron are usually Si 4+ However, the octahedra are centered with divalent or trivalent metal cations: in the case of divalent cations, all octahedral centers are occupied by cations, whereas in the case of trivalent cations, only 2 / 3 of the octahedra are occupied, thus balancing the charge.
[0070] Si in tetrahedron 4+ is trivalent Al 3+ and the trivalent cations in the octahedra are replaced by divalent cations and the divalent cations by monovalent cations, which results in a negative charge in the smectite layers, and metal cations are carried between the layers to counteract this negative charge. The metal cations supported between the smectite layers are usually coordinated with water.
[0071] When silver nitrate is added to a few percent of montmorillonite suspension and stirred and mixed, a cation exchange reaction occurs to produce silver ion-supported montmorillonite. The silver ions attached to the particle surfaces are washed and dried to obtain silver ion-supported montmorillonite. However, in this case, there is a problem of blackening due to precipitation of silver ions. To prevent the elution of silver ions, the silver ions can be chelated, which not only prevents the precipitation of silver ions but also makes the silver-supported montmorillonite hydrophobic.
[0072] A typical example of a chelating material is 2-(4-thiazolyl)benzimidazole. Another method is to replace the water coordinated between the layers of montmorillonite with other polar molecules. To do this, acrylonitrile, a polymerizable polymer, is polymerized to form polyacrylonitrile, which does not leave between the layers of montmorillonite.
[0073] In addition to the above, magnesium aluminometasilicate powder with silver and zinc supported thereon can be used as an antiviral agent in the same way as zeolite and montmorillonite. Compared to Y-type zeolite in aluminometasilicate, the amount of silver solute is extremely small. The chemical formula for magnesium aluminometasilicate is shown in the following formula (2). (2)Al2O3·MgO·SiO2×H2O
[0074] Here, the amount of Ag contained in the montmorillonite is about 5% by weight. The content of the montmorillonite carrying silver as an antiviral agent relative to 100 parts by mass of the base resin is 1 to 8 parts by mass, preferably 1 to 6 parts by mass. The reasons for specifying these numerical values are the same as those for zeolite.
[0075] (borate glass) Glass is an inorganic polymer composed of ions that exhibit a network structure and modified ions, and its composition can be continuously changed to give it solubility. There is an antiviral agent that combines borate glass (Na2O-SiO2-B2O3), which has a low durability due to the continuously changing composition, with ionized metals.
[0076] Specifically, borate glass, which is a combination of silver, copper, and zinc, can be used as an antiviral agent. In the case of this antiviral agent, when moisture is present, metal ions are eluted in extremely small amounts, thereby exerting its antiviral function.
[0077] (Surfactant) The extruded polyolefin resin foam of the present invention may contain a surfactant together with the base resin and the antiviral agent. In the present invention, the surfactant is allowed to be contained in an amount of 0.5 to 4 parts by mass.
[0078] Here, by including a surfactant in the resin, it is possible to impart hydrophilicity to the surface of the hydrophobic resin, as compared with the case of the resin alone. In addition, the surfactant is expected to have the effect of improving the dispersibility of the antiviral agent.
[0079] The reason for adding a surfactant to the base resin is as follows: The surface of the resin foam that is the base material according to this embodiment is generally hydrophobic, and if it remains hydrophobic regardless of the type of genome or the presence or absence of an envelope, the antiviral agent will not easily come into contact with and adhere to the virus surface.
[0080] Therefore, by adding a surfactant to the resin foam, the surface properties of the resin foam that constitutes the antiviral / antibacterial layer are changed from hydrophobic to hydrophilic, making it easier for viruses to be adsorbed onto the antiviral layer. As a result, the antiviral / antibacterial effects of the antiviral agent can be efficiently exerted.
[0081] Polyolefin resins such as polyolefin-based polyethylene and polypropylene are crystalline resins that contain crystalline and amorphous parts. Since the crystalline parts of the resin have high strength, the surfactant that is kneaded into the resin avoids the crystalline parts of the resin and migrates to the surface via the amorphous parts, and bleeds out to the surface of the resin foam, allowing the surfactant to act effectively in the surface layer.
[0082] In the present invention, the content of the surfactant in the polyolefin resin film in the polyolefin resin film layer is not particularly limited and can be set appropriately, but if it is less than 0.2 parts by mass, hydrophilicity is insufficient and viruses are difficult to adsorb, and if it is more than 4.0 parts by mass, bubble generation becomes unstable and tackiness occurs on the resin surface, so the range of 0.5 parts by mass to 4.0 parts by mass is preferable, and more preferably 1.0 parts by mass to 4.0 parts by mass.
[0083] The surfactant in the present invention includes various surfactants, which are classified into ionic surfactants that exhibit ionicity when dissociated in water and nonionic surfactants that are nonionic surfactants that do not ionize when dissolved in water. Furthermore, ionic surfactants can be classified into cationic surfactants, anionic surfactants, and amphoteric surfactants.
[0084] Specifically, for example, anionic surfactants include fatty acid salts such as sodium fatty acid, alkyl sulfates, alkyl sulfonates, and phosphate salts, cationic surfactants include primary, secondary, and tertiary amine salts, quaternary ammonium salts, and pyridium salts, and amphoteric surfactants include carboxylic acid types, sulfonate types, and phosphate salt types that have anionic and cationic hydrophilic groups in the molecule. As anionic surfactants, calcium stearate can be used as a fatty acid salt.
[0085] As for the nonionic surfactants, the polyethylene glycol type (polyoxyethylene type: EO type) includes alkyl polyoxyethylene ether, fatty acid polyoxyethylene ester, polypropylene glycol EO adduct, etc., and the polyhydric alcohol type includes fatty acid sorbitan ester, sucrose fatty acid ester, fatty acid polyglycerin ester, etc. For example, Riken Vitamin's glycerin fatty acid ester-based Rikemal S-100, etc. can be used as a nonionic surfactant.
[0086] (Crosslinking agent) Crosslinking agents are used to adjust the viscosity of the resin in a molten state during foaming to obtain a stable foamed state. Examples of organic peroxides used as crosslinking agents include dicumyl peroxide, 2,5-dimethyl-2,5-di-(t-butylperoxy)hexane, 2,5-dimethyl-2,5-di-(t-butylperoxy)hexyne-3, α,α'-bis(t-butylperoxydiisopropyl)benzene, t-butylperoxycumene, 4,4'-di(t-butylperoxy)valeric acid n-butyl ester, 1,1-di(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(t-butylperoxy)cyclohexane, and di-t-butyl peroxide.
[0087] If the amount of organic peroxide is small, the strength of the cell membrane is small and it is difficult to form closed cells during foaming, and if the amount of organic peroxide is large, the growth of the cell membrane is inhibited and only a foam with a low expansion ratio can be obtained. In the present invention, an organic peroxide is used as a crosslinking agent, and the amount of the organic peroxide used as a foaming agent is usually 0.3 to 2.0 parts by mass, preferably 0.5 to 1.5 parts by mass, per 100 parts by mass of polyolefin resin, but since it is closely related to the content of the foaming agent, it may be determined in consideration of the content of the foaming agent. As the crosslinking agent, dicumyl peroxide can be preferably used.
[0088] (foaming agent) In the present invention, the foaming agent may be an inorganic foaming agent, but it is preferable to use an organic pyrolytic foaming agent that decomposes when heated to generate gas.
[0089] Examples of such foaming agents include azodicarbonamide (ADCA), oxybisbenzenesulfonylhydrazide (OBSH), N,N'-dinitrosopentamethylenetetramine (DPT), p-toluenesulfonylhydrazide, benzenesulfonylhydrazide, diazoaminobenzene, N,N'-dimethyl-N,N'-dinitroterephthalamide, azobisisobutyronitrile, etc. These may be used alone or in combination of two or more.
[0090] In particular, when at least one selected from the group consisting of azodicarbonimide, N,N'-dinitrosopentamethylenetetramine, and oxybisbenzenesulfonylhydrazide is used in a predetermined amount, a foam with a high expansion ratio can be easily obtained. The amount of the foaming agent is preferably in the range of 5 to 40 parts by mass relative to 100 parts by mass of the polyolefin resin, and the amount of the foaming agent added may be determined in consideration of the resin material and the expansion ratio, and the amount of the foaming agent added is more preferably in the range of 10 to 40 parts by mass. In particular, azodicarbonamide (ADCA) is particularly preferably used as the foaming agent.
[0091] (Antioxidants, stabilizers, weatherproofing agents) The polyolefin-based extruded resin foam of the present invention may contain an antioxidant, a light stabilizer, a weathering agent, etc., as necessary. It is preferable to contain an antioxidant. In particular, when the antiviral agent to be blended is an antiviral agent containing a metal compound, it is preferable to contain an antioxidant. Blending an antioxidant can prevent oxidative deterioration of the base resin constituting the foam. Antioxidants include phenol-based antioxidants, phosphite-based antioxidants, blend-based antioxidants in which a phenol-based antioxidant and a phosphite-based antioxidant are blended, and thioether-based antioxidants. First, when a phenol-based antioxidant is added, it captures and decomposes peroxy radicals and hydroperoxides, which are the main causes of thermal oxidative deterioration, to suppress deterioration in the quality of the resin, and the phenol-based antioxidant, which is effective in preventing photodegradation when used in combination with a light stabilizer, has excellent antioxidant ability by capturing radicals generated by autoxidation. In particular, when used in combination with a phosphite-based antioxidant or a thioether-based antioxidant, which is a peroxide decomposer, it is possible to effectively prevent thermal oxidative deterioration of the resin. Thioether-based antioxidants have peroxide decomposition ability, and when used in combination with phenol-based antioxidants, they exhibit a remarkable synergistic effect, making it possible to impart excellent long-term thermal stability to resins.
[0092] Antioxidants that satisfy the above requirements include hindered phenol-based antioxidants such as tetrakis[methylene-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, and 4,4'-thiobis(3-methyl-6-t-butylphenol); )piperidinyl]siloxane, polyester of 4-hydroxy-2,2,6,6-tetramethyl-1-piperidineethanol and succinic acid, hindered amine compounds such as poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}], etc. The above oxidation inhibitors have an effect as a stabilizer or weather resistance agent in addition to an effect as an antioxidant. For example, in the present invention, specifically, Irganox1010 manufactured by BASF is used as tetrakis[methylene-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane.
[0093] The preferred content of the antioxidant is 0.05 to 1 part by mass relative to 100 parts by mass of the polyolefin resin. If the content of the antioxidant is high, crosslinking of the base resin is inhibited and the viscosity is reduced, so that the bubble diameter becomes large, and gas escape occurs, which may reduce the expansion ratio. Therefore, the upper limit of the content within the range that does not inhibit crosslinking is preferably 1 part by mass or less, and more preferably 0.8 parts by mass or less. Since the antioxidant is effective even with a small amount of content, it is sufficient that the content is 0.05 parts by mass or more, but if the content is less than this, the effect of the antioxidant is insufficient, so the antioxidant needs to be contained at least 0.05 parts by mass or more, but it is preferable to appropriately adjust the content within the above range depending on the type of antioxidant, stabilizer, or weathering agent and the use of the polyolefin foam. The antioxidant may be an antioxidant having metal inactivation ability.
[0094] Such antioxidants include Irganox MD1024 (2',3-bis{3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl}hydrazine, manufactured by BASF), Adekastab CDA-10 (N,N'-Bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, manufactured by ADEKA). The resin foam of the present invention may contain a metal deactivator. The metal deactivator may be an antioxidant having metal deactivating ability. Examples of metal deactivators include Irganox MD1024 (2',3-bis{3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl}hydrazine, manufactured by BASF), Adeka STAB ZS-27 (main component: 1,3,5-triazine-2,4,6-triamine, manufactured by ADEKA), and Adeka STAB CDA-1 (2-hydroxy-N-1H-1,2,4-triazol-3-ylbenzamide, manufactured by ADEKA).
[0095] (Flame retardants and other additives) The resin foam of the present invention may further contain other additives such as a flame retardant, a lubricant, a pigment, a dye, a plasticizer, a filler, a metal deactivator, an antistatic agent, etc. As these additives, known commercially available additives can be used.
[0096] Examples of the flame retardant include metal hydroxides, phosphorus-based flame retardant stabilizers, and halogen-based flame retardants. In order to improve flame retardancy, resins such as ethylene-based copolymers such as ethylene-vinyl acetate copolymers and ethyl acrylate copolymers may be included. Examples of the metal hydroxide include magnesium hydroxide and aluminum hydroxide. These metal hydroxides may or may not be surface-treated.
[0097] Examples of phosphorus-based flame retardants include compounds having a phosphorus atom in the molecule, and examples of such compounds include phosphorus oxides such as red phosphorus, phosphorus trioxide, phosphorus tetroxide, and phosphorus pentoxide; phosphoric acid compounds such as phosphoric acid, phosphorous acid, hypophosphorous acid, metaphosphoric acid, pyrophosphoric acid, and polyphosphoric acid; ammonium phosphates such as monoammonium phosphate, diammonium phosphate, and ammonium polyphosphate; phosphates such as melamine phosphates such as melamine monophosphate, melamine diphosphate, and melamine polyphosphate; aliphatic phosphate esters; and aromatic phosphate esters.
[0098] Examples of halogen-based flame retardants include brominated aliphatic or alicyclic hydrocarbons such as hexabromocyclododecane, brominated aromatic compounds such as hexabromobenzene, ethylenebispentabromodiphenyl, and 2,3-dibromopropylpentabromophenyl ether, brominated bisphenols and their derivatives, brominated bisphenol derivative oligomers, brominated aromatic compounds, chlorinated paraffins, chlorinated naphthalenes, chlorinated aromatic compounds, chlorinated alicyclic compounds, hexabromophenyl ether, and decabromodiphenyl ether.
[0099] To improve processability, oil components and various additives can be included, such as paraffin, modified polyethylene wax, stearates, hydroxystearates, vinylidene fluoride copolymers such as vinylidene fluoride-hexafluoropropylene copolymers, and organic modified siloxanes.
[0100] The extruded polyolefin resin foam of the present invention may contain various pigments, dyes, and carbon black. It may further contain titanium oxide. Titanium oxide contributes to improving antiviral properties and weather resistance.
[0101] The resin foam of the present invention can be obtained by adding a foaming agent and a crosslinking agent to a polyolefin resin, and extruding and foaming under predetermined conditions to obtain a resin foam having closed cells with a high expansion ratio. A crosslinking assistant may be added as necessary. In the present invention, in order to obtain a resin foam having antiviral properties, it is necessary to add a predetermined amount of a predetermined antiviral agent, surfactant, or antioxidant to the base resin as necessary, and change the content of the foaming agent, crosslinking agent, etc. according to the expansion ratio of the extruded polyolefin resin foam.
[0102] For example, when the base resin is a low-density polyolefin, the contents of the foaming agent and crosslinking agent are 15 parts by mass and 0.5 parts by mass, respectively, relative to 100 parts by mass of the base resin when the expansion ratio is 20 times, and 25 parts by mass and 1.0 part by mass, respectively, relative to 100 parts by mass of the base resin when the expansion ratio is 40 times. The average cell diameter of the polyolefin-based extruded resin foam of the present invention, excluding the skin layer, is 200 μm to 1500 μm, preferably 400 μm to 800 μm.
[0103] (Method of manufacturing resin foam containing antiviral agent) In the present invention, a masterbatch may be used to produce an extruded polyolefin resin foam containing an antiviral agent, or pellets obtained by compounding a base resin and an antiviral agent may be used, or a direct blending method in which the antiviral agent is directly blended may be used; however, production by the masterbatch method or compound method is preferable because a stable dispersed state is more likely to be obtained during product molding.
[0104] Master batches are made by mixing the antiviral agent with a surfactant, antioxidant, etc. (described later) and resin, and kneading and granulating the antiviral agent at a high concentration with the polyolefin resin in a twin-screw or single-screw kneading extruder. Usually the master batch is transported forward by a screw, plasticized, homogenized, pressurized, and made uniform.
[0105] The molten resin containing the antiviral agent homogenized in the kneading extruder is extruded as a strand through a die of the extrusion head. This strand is cut to obtain a master batch. In this case, for example, if the number of parts of the antiviral agent blended is 20 parts per 100 parts of polyolefin resin, a master batch containing 20 parts of antiviral agent particles can be produced. In this case, the concentration of the master batch must be controlled very carefully.
[0106] In the compound method, additives such as antiviral agents, resins, surfactants, and antioxidants may be added as necessary. After mixing these additives with the resin, the mixture is kneaded and extruded to prepare a pellet-shaped compound as a preform. This compound is then extruded and foamed to produce a resin foam.
[0107] In the polyolefin-based extruded resin foam of the present invention, additives such as an antiviral agent, a surfactant, an antioxidant, etc. may be added to the base resin depending on the purpose. These additives can be melt-kneaded with the base resin and extruded, and crosslinked and foamed at the same time during extrusion.
[0108] In this method, a resin composition obtained by compounding a polyolefin resin with additives such as an antiviral agent, a surfactant, and an antioxidant, as well as an organic decomposition type foaming agent and a crosslinking agent, is kneaded in a kneading machine such as a pressure kneader or a two-roll mixer, and extruded into a foaming base sheet of desired thickness and width in an extruder. The resulting mixture is then introduced into a heating furnace at about 200 to 230°C for foaming.
[0109] Any antiviral agent can be used as the antiviral agent here, but it is preferable to use inorganic compounds containing heavy metals such as silver and copper in some form, such as heavy metal compound fine particles, zirconium phosphate exchanged with silver or silver compounds, phosphate compounds complexed with calcium and zinc carrying silver or silver ions, zeolite carrying silver or copper by ion exchange, and montmorillonite carrying silver. 。
[0110] (Polyurethane foam cell structure and distribution of antiviral particles) The surface of the extruded sheet-shaped resin foam has a predetermined bubble diameter depending on the type of base resin and the expansion ratio. A non-foamed layer called a skin layer is formed near the surface of the sheet-shaped resin foam. A foamed bubble structure is observed in the rest of the sheet. The size of the bubbles near the center and near the surface in the thickness direction of the sheet is generally slightly larger near the center than near the surface.
[0111] Here, let us consider the distribution of the antiviral agent inside the foam of the present invention. In this case, since the antiviral agent is three-dimensionally dispersed approximately evenly in the thickness direction and the planar direction before foaming, the manifestation of the antiviral effect of the antiviral agent is premised on contact with the virus, and therefore only the antiviral agent exposed on the surface of the resin foam can manifest the antiviral effect. The base resin before foaming is in a bulk state, but during foaming, the bubble walls receive the pressure of the gas in the bubbles from both sides, and each bubble wall becomes thinner as the bubbles grow, and the growth of the bubbles stops at a predetermined bubble diameter where the pressure in the bubbles and the deformation resistance of the resin are balanced.
[0112] Next, looking at the behavior of the bubble walls of the antiviral agent particles during the foaming process, when the antiviral agent in the resin forms a porous cell structure from a three-dimensional bulk form due to bubble growth, the cell walls are formed while being subjected to pressing force from the gas inside the bubbles when the melt viscosity of the resin is high, and therefore there is almost no falling off of the antiviral agent particles during the bubble growth process.
[0113] Furthermore, as a result of the bubble walls forming a thin-walled porous body with a network structure, there is a competition between an increase in the probability distribution density of the number of antiviral agent particles near the bubble wall surface due to the thinning of the bubble walls and a decrease in the probability distribution density due to an increase in the surface area of the bubble walls as the bubbles grow; however, it is thought that the effect of the increase in the probability distribution density of the number of antiviral agent particles near the bubble wall surface becomes dominant, resulting in an increase in the number of particles near the foamed bubble walls.
[0114] Thus, when Novalon was used to observe the number of antiviral agent particles per specified area on the sliced cell wall surface and the skin layer on the foam surface with a scanning electron microscope, it was confirmed that the number of antiviral agent particles near the cell wall surface was greater than that in the skin layer near the foam surface.
[0115] This result is for Novalon, which is made of zirconium phosphate carrying Ag, and it means that the antiviral agent particles kneaded into the base resin before foaming have a larger effect of increasing the probability distribution density of the number of antiviral agent particles near the surface of the bubble wall due to thinning of the bubble wall than the effect of decreasing the probability density due to the increase in the surface area of the bubble wall caused by the growth of the bubble. In addition, the antiviral agent particles in the skin layer are embedded inside the skin layer, and are characterized in that the number of particles exposed on the extreme surface layer of the skin layer is small. Therefore, the present invention can be suitably used not only in the case of a low expansion ratio of 10 times or less, but also in the case of a high expansion ratio of 20 to 40 times.
[0116] As described above, it was confirmed that the probability density of the presence of antiviral agent particles increases when the cell walls of the foam are thinned and microscopically stretched during foaming. Here, since the above results are the relationship between the foaming behavior of the resin foam and the dispersed particles of the antiviral agent, it is considered that a similar relationship will hold unless the size of the antiviral agent particles changes drastically. Therefore, in the present invention, a resin foam with the cell wall surface exposed can be obtained by slicing the foam.
[0117] (Slicing and foam rolling) The extruded polyolefin resin foam of the present invention can be sliced to form a sheet-like resin foam with the cell surface cut and exposed. For example, the sheet-like foam obtained by extrusion and foaming can be sliced in the extrusion direction, i.e., parallel to the longitudinal direction of the sheet-like foam and the planar direction of the sheet-like resin foam, to form the resin foam of the present invention. The sliced surface is not limited to a direction parallel to the resin foam, and may be a wavy surface, or a surface formed by slicing once may be subjected to secondary processing to form a new cell opening surface.
[0118] There are three possible slicing methods. By slicing the vicinity of the surface layer of the foam, the skin layer, which is the unfoamed layer near the surface layer, is removed and the cell walls are exposed at the same time, thereby imparting antiviral properties to the foam. Alternatively, by slicing the vicinity of the center in the thickness direction of the foam, the cell walls can be exposed, which makes it possible to impart antiviral properties to the foam. Furthermore, by slicing the foam while passing it through a profile roll, it is possible to impart antiviral properties while expressing design by forming an uneven pattern on the foam corresponding to the unevenness of the roll. In particular, by passing it through a profile roll to form an uneven pattern on the sliced surface, it becomes applicable to mats for evacuation shelters, etc. Slicing is not limited to the vicinity of the center in the thickness direction of the foam, and it is also possible to slice a position offset by a predetermined distance from the center.
[0119] The extruded resin foam is then rolled with one or more rolls while applying tension to the product in order to adjust the surface condition and dimensions. This causes the bubbles to change from a nearly isotropic state to a slightly flattened shape in the rolling direction. During this process, the foam also stretches in length. The rolling rate is usually set in the range of 5% to 15%.
[0120] When examining the change in bubble structure due to roll rolling, it is believed that when bubbles are flattened by roll rolling, the extension angles of the bubble walls at the triple and quadruple junctions, which are the boundaries between the bubble walls, are plastically deformed and change in shape due to stress concentration caused by shear strain during roll rolling, resulting in flattening. However, if the rolling is light in order to smooth the surface, much of the rolling amount elastically recovers immediately after rolling, and so there is no significant effect on the shape of the bubbles.
[0121] Regarding the cell structure after rolling, although the unfoamed layer near the surface becomes slightly thinner by passing through the rolls than by rolling, most of the foamed layer recovers elastically after passing through the rolls, so there is only a very slight expansion, with almost no effect on the shape of the cells. Even if the cells expand slightly, the depth from the opening of the cell to the bottom of the cell wall becomes shallower by that amount, and the presence ratio of the cell wall near the opening increases, so in reality, the average presence probability of the antiviral agent particles near the openings does not change, and it is considered that there is almost no substantial effect on the antiviral properties. Effect of the Invention
[0122] According to the present invention, since the probability density of the antiviral agent present on the surfaces of the bubbles of the sliced foam after foaming is increased compared to the probability density of the antiviral agent on the surface of the foam and on the surface of the base material before foaming, it is possible to obtain a polyolefin-based extruded resin foam having a sliced surface with high antiviral properties, and a method for producing the polyolefin-based extruded resin foam. Agent In addition, the present invention utilizes the surface appearance effect of the antiviral agent on the bubble wall surface. , issue It can also be suitably used for extruded resin foams with a high foaming ratio of 20 to 40 times. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS EXAMPLES
[0123] The present invention will be described in further detail below with reference to examples. (Example) The base resin was a polyolefin resin, and a material was used in which a predetermined amount of one of the following was blended within the range of 1 to 8 parts by mass: zirconium phosphate ion-exchanged with silver or silver compounds, a phosphate compound containing calcium and zinc ion-exchanged with silver or silver compounds, a zeolite carrying silver or copper by ion exchange, or a montmorillonite compound carrying silver was blended within the range of 1 to 8 parts by mass as an antiviral agent, and a surfactant was further added within a predetermined range of 0.1 to 4 parts by mass to produce resin foams with an expansion ratio of 30 times as shown in Tables 1 to 4. Furthermore, in Test Example 5, resin foams were produced by adding a predetermined amount of antioxidant to resin foams with different types of base resins and expansion ratios of 20 times and 40 times. For example, 0.9 parts by mass of crosslinking agent and 11 parts by mass of foaming agent were added for a 20 times expansion ratio, and 0.7 parts by mass of crosslinking agent and 22 parts by mass of foaming agent were added for a 40 times expansion ratio. In Test Examples 6 and 7, the effects of adding a small amount of each antiviral agent, adding a predetermined amount of antiviral agent, and adding an amount of surfactant that is less than the desired range, and adding an excessive amount of surfactant were evaluated.
[0124] Furthermore, low-density polyolefin (LDPE) was used as the base resin, and an organic decomposition type foaming agent and crosslinking agent were added to LE200M manufactured by Japan Polyolefins Co., Ltd., and the mixture was kneaded and pelletized in a pressure kneader to obtain pellets of a foamable resin composition. The pellets were fed from the hopper of a single-screw extruder, melt-kneaded in the extruder, and extruded through a die of a specified width to obtain a smooth foaming base material sheet having a thickness of 4 mm.
[0125] Next, this foaming base sheet was extruded at 120-150°C and then continuously passed through a heating furnace at 220-240°C to expand it 30 times, and then passed through a roll to adjust the dimensions and surface properties of the foam, yielding a sheet-like foam of approximately 12 mm. To obtain this sheet foam, 0.8 parts by mass of Percmyl D dicumyl peroxide (trade name, manufactured by Nippon Oil & Fats Co., Ltd.) was used as the crosslinking agent, and 16 parts of Vinihole AC#LQ (azodicarbonamide (ADCA)) manufactured by Eiwa Kasei Co., Ltd. was used as the foaming agent, which is an organic decomposition type foaming agent. Here, this sheet foam was sliced to obtain a sliced surface so that the central part of the thickness of the sheet foam would be the evaluation surface of the test material, and test pieces were cut out from this sliced surface and used for a test to evaluate antiviral properties.
[0126] (Test Example 1) (Evaluation of the effect of zirconium phosphate supported with silver or silver compounds by ion exchange on the antiviral properties) Polyolefin foams were prepared using 100% by weight of low-density polyethylene as the base resin, and containing 1.2 parts by mass, 2.0 parts by mass, 3.5 parts by mass, 6.0 parts by mass, and 8.0 parts by mass of Toa Gosei's Novalon IV1000, an antiviral agent consisting of zirconium phosphate ion-exchanged with silver or a silver compound, expanded 30 times, relative to 100 parts by mass of the base resin. These were designated Examples 1 to 5, respectively.
[0127] Polyolefin-based extruded resin foams were prepared using 100% by weight of low-density polyethylene as the base resin, containing 6 parts by mass of Toa Gosei's Novalon IV1000, an antiviral agent consisting of zirconium phosphate ion-exchanged with silver or a silver compound, per 100 parts by mass of the base resin, and further containing 0.5 parts by mass, 2.0 parts by mass, and 4.0 parts by mass of Riken Vitamin's glycerin fatty acid ester-based Rikemal S-100 as a surfactant, and are designated as Examples 6, 7, and 8, respectively.
[0128] Example 9 was prepared by changing the surfactant from Rikemar S-100 to a material containing 2 parts by mass of calcium stearate, another surfactant, instead of Rikemar S-100, in comparison with the material containing 6 parts by mass of Novalon IV1000 as an antiviral agent and 2 parts by mass of Rikemar S-100 as a surfactant in Example 7. Next, Example 10 was prepared by increasing the amount of the antiviral agent to 8 parts by mass as in Example 5, and further adding 4 parts by mass of Rikemar S-100 as a surfactant.
[0129] (Test Example 2) (Evaluation of the antiviral effect of phosphate compounds consisting of hydroxyapatite containing silver or calcium and zinc carrying silver ions) Polyolefin foams were prepared using 100% by weight of low-density polyethylene as the base resin, and the antiviral agent was expanded 30 times to contain 1.2 parts by mass, 2.0 parts by mass, 3.5 parts by mass, 6.0 parts by mass, and 8.0 parts by mass of a phosphate compound made of hydroxyapatite composition containing calcium and zinc with silver or a silver compound supported by ion exchange per 100 parts by mass of the base resin. These were designated Examples 11 to 15, respectively.
[0130] Polyolefin extruded resin foams were prepared by using 100% by weight of low-density polyethylene as the base resin and foaming it 30 times to contain a phosphate compound made of a hydroxyapatite composition containing calcium and zinc supported by silver or silver compound ion exchange, 6 parts by mass per 100 parts by mass of the base resin, and further containing 0.5 parts by mass, 2.0 parts by mass, or 4.0 parts by mass of calcium stearate as a surfactant. These were designated Examples 16, 17, and 18, respectively.
[0131] Example 19 was prepared by changing the material containing 6 parts by mass of a phosphate compound made of a hydroxyapatite composition containing calcium and zinc supported by silver or silver compound ion exchange as the antiviral agent in Example 17 and 2 parts by mass of calcium stearate as the surfactant to a material containing 2 parts by mass of Rikemal S-100. Next, the amount of the antiviral agent was increased to 8 parts by mass as in Example 15, and Example 20 was prepared by further adding 4 parts by mass of calcium stearate as the surfactant.
[0132] (Test Example 3) (Evaluation of the antiviral properties of ion-exchanged zeolites containing silver and copper) As in the case of zirconium phosphate, 100% by weight of low-density polyethylene was used as the base resin, and polyolefin foams were prepared containing 1.2 parts by mass, 2.0 parts by mass, 3.5 parts by mass, 6.0 parts by mass, and 8.0 parts by mass of Sinanen's AC10D, an antiviral agent consisting of ion-exchanged zeolite containing silver and copper, expanded 30 times, relative to 100 parts by mass of the base resin, and these were designated Examples 21 to 25, respectively.
[0133] Similarly, polyolefin extruded resin foams were prepared using 100% by weight of low-density polyethylene as the base resin, and containing 6 parts by mass of Sinanen's AC10D, which was expanded 30 times and contained ion-exchanged zeolite containing silver and copper, per 100 parts by mass of the base resin, and further containing 0.5 parts by mass, 2.0 parts by mass, and 4.0 parts by mass of Riken Vitamin's glycerin fatty acid ester-based Rikemal S-100 as a surfactant. These were designated Examples 26, 27, and 28, respectively.
[0134] Example 29 was prepared by changing the surfactant to a material containing 2 parts by mass of calcium stearate instead of the material containing 6 parts by mass of Sinanen AC10D as an antiviral agent and 2 parts by mass of Rikemal S-100 as a surfactant in Example 27. Next, Example 30 was prepared by increasing the amount of zeolite as an antiviral agent in the material in Example 28 to 8 parts by mass as in Example 5, and further adding 4 parts by mass of a surfactant.
[0135] (Test Example 4) (Evaluation of antiviral properties of silver-loaded montmorillonite compounds) Similarly to the case of zeolite, 100% by weight of low-density polyethylene was used as a base resin, and polyolefin foams were prepared in which the antiviral agent was expanded 30 times and comprised a montmorillonite compound carrying silver, and the antiviral agent was contained in amounts of 1.2 parts by mass, 2.0 parts by mass, 3.5 parts by mass, 6.0 parts by mass, and 8.0 parts by mass per 100 parts by mass of the base resin. These were designated Examples 31 to 35, respectively.
[0136] Similarly, polyolefin-based extruded resin foams were prepared using 100% by weight of low-density polyethylene as the base resin, and containing a polyolefin foam expanded 30 times and containing 6 parts by mass of a silver-loaded montmorillonite compound per 100 parts by mass of the base resin, and further containing 0.5 parts by mass, 2.0 parts by mass, or 4.0 parts by mass of Riken Vitamin's glycerin fatty acid ester-based Rikemal S-100 as a surfactant. These were designated Examples 36, 37, and 38, respectively.
[0137] Example 39 was prepared by changing the material containing 6 parts by mass of a montmorillonite compound carrying silver as an antiviral agent and 2 parts by mass of Rikemal S-100 as a surfactant of Example 37 to a material containing 2 parts by mass of calcium stearate. Next, the amount of zeolite as an antiviral agent was increased to 8 parts by mass as in Example 35, and Example 40 was prepared by further containing 4 parts by mass of Rikemal S-100 as a surfactant.
[0138] (Test Example 5) (Evaluation of the impact of base resin type, foaming ratio, and antioxidant on antiviral properties) In the embodiment of Test Example 5, 100% by weight of low-density polyethylene was used as the base resin, and a mixed resin foam of 80% by weight of low-density polyethylene and 20% by weight of high-density polyethylene was foamed 30 times. The same antiviral agent as in Example 7 contained 6.0 parts by weight of Novalon IV1000 manufactured by Toa Gosei relative to 100 parts by weight of the base resin, and further contained 2.0 parts by weight of Rikemal S-100, a glycerin fatty acid ester-based surfactant manufactured by Riken Vitamin. A polyolefin-based extruded resin foam was produced and designated as Example 41. In Example 41, LE200M manufactured by Japan Polyolefins Co., Ltd. was used as the low-density polyethylene, and HD1300 manufactured by Japan Polyolefins Co., Ltd. was used as the high-density polyethylene.
[0139] Example 42 is an example in which the base resin of the resin foam was changed from low-density polyethylene to polypropylene. Since polypropylene is difficult to crosslink by chemical crosslinking, it was extruded and crosslinked by electron beam by the electron beam crosslinking method, and then expanded 30 times under specified conditions. The composition of the antiviral agent and surfactant in this example is the same as that of Example 17. In Examples 43 and 44, the expansion ratio was set to 20 times and 40 times, respectively, and the antiviral agent, surfactant, etc. were the same as those of Example 7. In Example 45, a material was prepared by adding 0.8 weight of Irganox 1010 as an antioxidant to a material of the same composition as Example 7.
[0140] (Test Examples 6 and 7) (Antiviral evaluation of under-addition of antiviral agents, under-addition of surfactants, and over-addition) Using low-density polyethylene as the base resin, 0.6 parts by mass of Toagosei's Novalon IV1000, an antiviral agent consisting of zirconium phosphate ion-exchanged with silver or a silver compound, was added to 100 parts by mass of the base resin, and the material was foamed 30 times to prepare a material designated as Example 46. Example 47 was a resin foam similar to that of Comparative Example 1, except that the antiviral agent in Example 46 was changed to a resin foam containing 0.6 parts by mass of a phosphate compound consisting of a hydroxyapatite composition containing calcium-zinc ion-exchanged with silver or a silver compound.
[0141] Example 48 was prepared by adding 0.3 parts by weight of Riken Vitamin's glycerin fatty acid ester-based Rikemal S-100 as a surfactant to Example 4, which was a material in which low-density polyethylene was used as the base resin and 6 parts by weight of Toagosei's Novalon IV1000 was added to 100 parts by weight of the base resin, and Example 49 was prepared by adding 0.3 parts by weight of calcium stearate as a surfactant to Example 14, which was a material in which 100% by weight of low-density polyethylene was used as the base resin and 6 parts by weight of a phosphate compound made of a hydroxyapatite composition containing silver or silver compound ion-exchanged calcium / zinc was added to 100 parts by weight of the base resin. Next, materials containing the surfactant in amounts ranging from 4 parts by weight to 5 parts by weight, which is larger than that, were prepared for Examples 8 and 18, and these materials were designated Examples 50 and 51.
[0142] A material containing 0.6 parts by mass of Sinanen's AC10D, an antiviral agent consisting of ion-exchanged zeolite containing silver and copper, was foamed 30 times using low-density polyethylene as the base resin to prepare a material as Example 52. Furthermore, a resin foam in which the antiviral agent was changed to a resin foam containing 0.6 parts by mass of a montmorillonite compound carrying silver was prepared as Example 53.
[0143] Example 54 was a material in which a small amount of Riken Vitamin's Rikemal S-100 (0.3 weight parts) was added as a surfactant to Example 24, which was a material in which low-density polyethylene was used as the base resin and the antiviral agent was 6 parts by mass of Sinanen's AC10D, an ion-exchange zeolite containing silver and copper. Example 55 was a material in which 100% by weight of low-density polyethylene was used as the base resin and 6 parts by mass of a silver-supported montmorillonite compound was added per 100 parts by mass of the base resin, and 0.3 weight parts of calcium stearate was added as a surfactant to Example 34.
[0144] In addition, for the materials containing 6 parts by mass of the antiviral agent of Examples 28 and 38, materials were prepared in which the content of each surfactant was increased from 4 parts by mass to 5 parts by mass, which is larger than that of the antiviral agent of Examples 28 and 38, and these were designated Examples 56 and 57.
[0145] (Anti-viral evaluation of profiled and secondary processed surfaces of resin foam) A resin foam containing the same base resin and antiviral agent and surfactant of the same composition as in Example 27 was produced, and a sample was cut out from the profiled surface to produce a test piece as Example 58. Furthermore, a test material with the same composition as in Example 7 and whose end was cut at an angle of 30° as a secondary processing step was produced to produce Example 59. In this case, the profiled surface was sampled as the wavy surface, so the surface area of the test piece was somewhat larger.
[0146] (Test Example 8) (Evaluation of antiviral effects of multiple antiviral agents and surfactants) In Table 8, in Test Example 8, test materials were prepared by appropriately combining two of the four types of antiviral agents used in the present invention, and these were designated Examples 60 to 64. Furthermore, test materials containing a combination of surfactants in addition to multiple antiviral agents were designated Examples 65 to 69, and the antiviral properties of these materials were evaluated.
[0147] (Comparative Example) A material was prepared by adding 1.2 weight parts of Irganox 1010 as an antioxidant to a material of the same composition as in Example 7, and this material was designated Comparative Example 1. Comparative Example 2 was prepared by taking a test piece for the antiviral test from the skin layer, not the sliced surface, of the material in Example 4, which was a material in which low-density polyethylene was used as the base resin and 6 parts by weight of Toa Gosei's Novalon IV1000 was added to 100 parts by weight of the base resin as the antiviral agent, and Comparative Example 3 was prepared by cutting a sample from the skin surface, not the sliced surface, of the material in Example 10, which was a material in which 8 parts by weight of Baron IV1000 was added to 100 parts by weight of the base resin as the antiviral agent, and 4 parts by weight of Riken Vitamin's Rikemal S-100 was added to the material.
[0148] Similarly, in the materials corresponding to Examples 14 and 20, which are phosphate compounds consisting of hydroxyapatite compositions containing calcium and zinc with an antiviral agent ion-exchanged with silver or a silver compound, samples were taken from the skin layer instead of from the sliced surface, to give Comparative Examples 4 and 5, respectively.
[0149] Comparative Example 6 was obtained by taking antiviral test specimens from the skin layer instead of the sliced surface of the material in Example 24, and Comparative Example 7 was obtained by cutting samples from the skin layer instead of the sliced surface of the material in Example 30. Comparative Examples 8 and 9 were obtained by taking samples from the skin layer instead of the sliced surface of the materials corresponding to Examples 34 and 40, respectively.
[0150] (Anti-viral test method) The antiviral test was basically performed in accordance with ISO21702. The test used influenza virus (H3N2, A / hongkong / 6 / 86) and MDCK cells (canine kidney tubular epithelial derived cells) as host cells, and was performed under the following conditions: sensitization temperature 25°C, sensitization time 24 hours. SCDLP medium was used as the washout solution, and the infectivity was measured using the plaque method.
[0151] The specific test procedure was as follows: three samples measuring 40 mm x 40 mm x 4 mm thick were cut out from each test material of each Example, and each was individually attached to the bottom of a separate petri dish. Next, 400 μL of virus was inoculated onto each sample, and then a PET film (4 cm x 4 cm) was placed over the sample. After the sensitization time had elapsed, 10 ml of washout solution was added and the samples were washed out by pipetting. Finally, the infectivity value V after 24 hours in the washout solution was measured. 24 Based on this, the percentage R (%) of the amount of virus that had decreased after 24 hours relative to the initial harvested amount V0 and the activity value Mv after 24 hours were calculated.
[0152] Specifically, assuming that the percentage of virus reduction after 24 hours is R (%) and the antiviral activity value is Mv, both can be calculated by the following formula using the initial infectivity immediately after inoculation and the infectivity titer 24 hours after inoculation. The percentage of the virus reduction amount after 24 hours relative to the initial virus amount R (%) was calculated using the following formula (3): (3) R = (V0 - V 24 ) / V0 The activity value of an antiviral agent can be calculated by the following formula (4). (4) Mv = log(V0) - log(V 24 ) Where, V0: initial infectivity immediately after inoculation, V 24 In the present invention, for convenience, the infectivity after 24 hours is expressed in logarithm as the virus infectivity logarithm (Log(PFU)) together with the activity value (originally logarithmic titer). By expressing it in this way, the sum of the logarithm of the infectivity after 24 hours and the activity value is always the logarithm of the initial infectivity, making it easier to confirm the relationship between the activity value and the infectivity. Here, the measured value of the initial infectivity is 1.70×10 6 The logarithmic titer of the initial infectivity was 6.23.
[0153] (Test Results) The test results are shown in Tables 1 to 8 below, showing the type of base resin, foaming ratio, test specimen collection position, type and amount of antiviral agent and surfactant, and three types of results obtained as antiviral test results for these: the logarithm of the infectivity value of the virus after 24 hours, the amount of virus reduced relative to the initial amount collected, and the activity value.
[0154] [Table 1]
[0155] [Table 2]
[0156]
Table 3
[0157]
Table 4
[0158]
Table 5
[0159]
Table 6
[0160]
Table 7
[0161]
Table 8
[0162]
Table 9
[0163]
Table 10
[0164] Tables 1 to 4 show the test results of the materials of each example on the sliced surface of the resin foam when the type of antiviral agent and the amount of surfactant added were changed, Table 5 shows the test results of each example for evaluating the influence of other base resin compositions, expansion ratios, and antioxidants on the antiviral effect, and Tables 6 and 7 show examples showing the influence of under-addition of antiviral agent and under-addition and over-addition of surfactant, and examples showing test results when the sliced surface was a profiled surface and a secondary processed surface. Table 8 shows examples showing test results when two types of antiviral agents or a combination of two types of antiviral agents and a surfactant were added.
[0165] Table 1 shows the test results when zirconium phosphate with silver or a silver compound ion-exchanged was added alone at different contents to the antiviral agent corresponding to Test Example 1, and when a surfactant was added in combination with this at different surfactant contents. Table 2 shows the test results when a phosphate compound made of a hydroxyapatite composition containing silver or silver ions supported by ion exchange, containing calcium and zinc, was added alone at different contents to the antiviral agent corresponding to Test Example 2, and when a surfactant was added in combination with this at different surfactant contents.
[0166] Table 3 shows the test results when the silver- and copper-containing ion-exchanged zeolite corresponding to Test Example 3 was added alone at different contents, and when it was combined with a surfactant at different contents. Table 4 shows the test results when the silver-supported montmorillonite compound corresponding to Test Example 4 was added alone at different contents, and when it was combined with a surfactant at different contents. There are no particular limitations on the surfactant used here as long as it can ensure dispersibility inside the resin foam, but in the examples corresponding to Test Examples 1 to 4 shown in Tables 1 to 4, either Riken Vitamin's glycerin fatty acid ester-based Rikemal S-100 or calcium stearate was used.
[0167] In Test Examples 1 to 4 in Tables 1 to 4, for any of the antiviral agents, the virus amount in the test material tends to decrease within a specified range as the content of the antiviral agent increases when the antiviral agent is in the range of 1.2 parts by mass to 8 parts by mass, but the inhibitory effect is greatest when the content of the antiviral agent is in the vicinity of 3.5 parts by mass, and this tendency slows down when the amount of the antiviral agent exceeds 3.5 parts by mass. Furthermore, it can be seen from the reduction in the virus amount and activity value that by increasing the surfactant content in the range of 0.5 parts by mass to 4 parts by mass when the amount of the antiviral agent is 3.5 parts by mass, the virus reduction effect becomes greater even when the content of the antiviral agent is the same.
[0168] Here, in the results of Test Examples 1 to 4, when the content of the antiviral agent is in the range of 1.2 parts by mass to 8 parts by mass, the amount of virus reduced from the initial intake is 95% or more, and the activity value exceeds 1.30. Also, when the content exceeds 2 parts by mass, the amount of virus reduced from the initial intake is 99% or more, and the activity value exceeds 2.0, showing that when the content of the antiviral agent is 2 parts by mass or more, stable antiviral properties are exhibited.
[0169] Furthermore, the antiviral effect was greatest at 3.5 parts by mass of the antiviral agent, and no increase in the virus quantity or activity value was observed even when the amount of the antiviral agent was increased beyond 3.5 parts. The reason for this is unclear, but it is thought to be due to factors such as uneven dispersion even when the amount of the antiviral agent is increased.
[0170] In order to examine the effect of the surfactant, for each Example from Test Example 1 to Test Example 4, materials were prepared to which 3.5 parts by mass of the antiviral agent and a specified amount of surfactant in the range of 0.5 to 4 parts by mass were added, and the relationship between the surfactant content and the effect of the antiviral agent was examined. As a result, it was found that within the range of up to 4 parts by weight, there was a tendency for the virus suppression effect to increase by adding the surfactant.
[0171] Examples 41 and 42 in Table 5 show the results when the base resin in Example 7 in Table 1 was changed from the low-density polyethylene to a mixed resin of low-density polyethylene and high-density polyethylene, and the results when it was changed to a polypropylene resin. However, there was only a slight difference in the amount of virus reduction due to the difference in base resin, and there was no large difference in the amount of virus reduction due to the difference in base resin.
[0172] As shown in Table 5, the compositions of the base resin, antiviral agent, and surfactant were the same as those of Example 7, but the reduction in the virus amount and the change in activity value of Example 43, which is a resin foam with an expansion ratio of 20, and Example 44, which is a resin foam with an expansion ratio of 40, showed slight differences compared to those of Example 7, but were not so large.
[0173] In the present invention, a metal-based antiviral agent supported on an inorganic substance is used as the antiviral agent, so the resin foam shown in Example 45 was produced by further adding 0.8 parts by mass of an antioxidant to prevent oxidative deterioration of the resin to the material of Example 7, and the antiviral effect of the antioxidant and its effect on the foaming behavior of the base resin were evaluated.
[0174] In Example 45, as in Example 7, the foaming state of the resin foam during and after foaming and the activity value of the antiviral effect were slightly decreased, but the activity value due to the antioxidant was not significantly affected, and it was confirmed that a predetermined antiviral effect was obtained. Therefore, there is no problem in adding an antioxidant as long as the amount of the antioxidant is within the range of 1 part by mass or less.
[0175] In the cases of Examples 46 and 47 in Table 6, and 52 and 53 in Table 7, the content of the antiviral agent was low at 0.6 parts by mass, and therefore the amount of virus reduction exceeded 90% or more but was less than 95%, and the activity value was also 2.00 or less. The antiviral effect was weaker than when the content of the antiviral agent was 1.2 parts by mass, but a certain antiviral effect was observed even when the content of the antiviral agent was 1 part by weight or less.
[0176] Furthermore, from the results of Examples 48 and 49 in Table 6 and Examples 54 and 55 in Table 7, when the surfactant content is 0.3 parts by mass, the dispersion effect and hydrophilization effect of the surfactant on the antiviral agent are insufficient, and the antiviral properties are almost unchanged compared to when only the antiviral agent is contained at 3.5 parts by mass. For this reason, when the surfactant content is 0.5 parts by mass or less, the effect of improving the antiviral properties due to the inclusion of the surfactant is not observed.
[0177] From the results of Example 50 and Example 51 in Table 6 and Example 56 and Example 57 in Table 7, it was confirmed that when a specified amount of antiviral agent is contained, adding 4 parts by mass or more of a surfactant or adding 5 parts by mass or more of a surfactant makes almost no difference in the amount of virus reduction and is meaningless.
[0178] The antiviral test results of the profile-processed surface and the secondary processed surface of Example 58 in Table 7 both showed almost the same virus reduction amount and activity value as Example 7. As a result, it was found that the resin foam obtained after extrusion crosslinking has antiviral agent particles exposed on the surface of the cell walls due to three-dimensional deformation of the cell walls during the foaming process, and therefore has the same effect whether the processed surface is a flat sliced surface or in any direction other than parallel to the sheet plane direction. From the above results, the polyolefin-based extruded resin foam of the present invention can be particularly suitably used for secondary processed products using this.
[0179] Table 8 shows various combinations in which two types of antiviral agents are contained and in which a surfactant is further added, and in the material of Test Example 8 in Table 8, the amount of virus reduction after 24 hours exceeded 99% in all cases, and the activity value also showed a range of 2.26 to 2.80. Specifically, the results when only the antiviral agents of Examples 60 to 64 in Table 8 were contained were similar to the results when each antiviral agent was added alone, with activity values in the range of 2.26 to 2.40, which is almost the same as the activity value range of 2.22 to 2.40 when 2 parts by mass or more of the antiviral agent was added alone in Test Examples 1 to 4.
[0180] Here, no synergistic effect between antiviral agents was observed, but no inhibitory effect was observed either, and the addition of multiple antiviral agents did have an increased effect. Also, as with the single addition of an antiviral agent, the antiviral effect decreased as the content of the antiviral agent increased.
[0181] In Examples 65 to 68, the activity values when two types of antiviral agents and a surfactant were added simultaneously were 2.52 to 2.82, and in comparison with the upper and lower limits of the activity values when an antiviral agent and a surfactant were used in combination in Test Examples 1 to 4, which were 2.35 to 3.00, the two were almost equivalent, and a synergistic effect of improving the antiviral effect by using an antiviral agent and a surfactant in combination was observed, just like when they were added alone.
[0182] In Table 9, Comparative Example 1, which is a material in which 1.2 weight percent of Irganox 1010 was added as an antioxidant to a material of the same composition as in Example 7, was considered to have a problem with the foaming state because the foaming inhibition by the antioxidant caused unstable parts of the product's bubble structure, and therefore there was no problem with the antiviral properties, but it was chosen as a comparative example because it lacked stability as a foamed product. Comparative Examples 2 to 5 in Table 9 and Comparative Examples 6 to 9 in Table 10 are materials containing 6 parts of the antiviral agent corresponding to Examples 4, 10, 14, 20, 24, 30, 34, and 40, respectively, and materials containing 8 parts of the antiviral agent and 4 parts of the surfactant, respectively. The antiviral properties of the skin layer, rather than the sliced surface of the resin foam, were evaluated based on the virus reduction amount and activity value, but even in the cases where the content of the antiviral agent or surfactant was high, the virus reduction amount did not exceed 90% of the initial collection amount, and the activity value did not exceed 1. The reason for this was presumably that in the skin layer, less of the antiviral agent was exposed on the material surface compared to when the foam layer was sliced to obtain a sliced surface, and the state of the antiviral agent in the two cases was different.
[0183] As described above, in the present invention, in a polyolefin-based extruded resin foam having an expansion ratio in the range of 20 to 40 times, the foam contains, as an antiviral agent, 1 to 8 parts by mass of an inorganic compound-based antiviral agent carrying a metal or metal compound, or such an antiviral agent plus 0.5 to 4.0 parts by mass of a surfactant, and the foam layer of the sliced material is sliced to expose the sliced surface. Test results showed that the sliced surface had excellent antiviral properties, as shown by the large virus reduction amount and high activity value.
[0184] The same conclusion was drawn not only from the evaluation of the amount of virus reduction from the initial intake amount as described above, but also from the results of the virus infectivity value (expressed logarithmically in this explanation) and the virus activity value after 24 hours. The reason why the sliced surface of the foam layer has superior antiviral properties compared to the skin layer on the surface of the foam is thought to be because the antiviral agent particles are more likely to be exposed to the surface of the bubble walls during the three-dimensional deformation of the bubble walls in the foaming process. This effect is confirmed by the test results on profile-processed surfaces and secondary processed surfaces, which show that the effect can be obtained regardless of the direction of slicing as long as the foam layer is sliced to open up, and the rationality of the mechanism of antiviral agent particles' exposure during three-dimensional deformation is also thought to be supported.
[0185] More specifically, this is thought to be because cell walls are formed while being subjected to pressing force from the gas inside the bubbles when the melt viscosity of the resin is high, so there is almost no falling off of the antiviral agent particles during the bubble growth process, and the increase in the probability distribution density of the number of antiviral agent particles near the bubble wall surface due to thinning of the bubble wall becomes dominant.On the other hand, the reason why it is difficult to obtain an effect even when the skin layer contains a high content of antiviral agent is thought to be because, unlike the bubble walls, the surface energy of the skin layer is high and the antiviral agent is easily embedded inside the skin layer.
[0186] Regarding the antiviral effect of a surfactant, an increase in antiviral activity was observed when a surfactant was added, but this is thought to be promoted by the combined effect of the surfactant improving the dispersibility of the antiviral agent, as well as the improved wettability due to improved hydrophilicity on the bubble surfaces, which increases the adsorption to viruses.
[0187] Furthermore, in the present invention, an inorganic compound-based antiviral agent carrying a metal or a metal compound is used. R Therefore, when the effect of including an antioxidant in the range of 1 part by mass or less was examined, it was confirmed that it was possible to improve the long-term durability of the resin without affecting the foaming property.
[0188] When the content of the antiviral agent exceeds 3.5 parts by mass, the effect of the agent decreases with increasing content. This is thought to be because the dispersion state of the antiviral agent becomes biased when the content exceeds 3.5 parts by mass. In addition, in terms of the effectiveness of each antiviral agent, zeolite supported with silver and copper by ion exchange was slightly superior to other antiviral agents. In addition, when comparing surfactants, Rikemal S-100 and calcium stearate, Rikemal S-100 was slightly superior.
[0189] Although the antiviral effects of antiviral agents and surfactants in resin foams have been described in the above embodiments of the present invention, the technical scope of the present invention is not limited to the above-described embodiments. It is clear that a person skilled in the art can come up with various modified or revised examples within the scope of the technical ideas described in the claims, and it is understood that these also naturally fall within the technical scope of the present invention.
Claims
1. A polyolefin-based extruded resin foam containing an inorganic antiviral agent, at least one surface of which is a sliced surface with open cell walls constituting a foam layer, the inorganic antiviral agent being exposed on the sliced surface, and the polyolefin-based extruded resin foam having a cell structure with an expansion ratio of 20 to 40 times and a closed cell structure with an average cell diameter of 200 to 1500 μm, The inorganic antiviral agent contained in the polyolefin-based extruded resin foam is any one of: (1) zirconium phosphate carrying silver or a silver compound by ion exchange; (2) a phosphate compound having a hydroxyapatite composition containing calcium and zinc carrying silver or silver ions by ion exchange; (3) zeolite carrying silver or copper by ion exchange; or (4) silver-carrying montmorillonite, An extruded polyolefin resin foam, comprising 1 to 8 parts by mass in total of at least one of the inorganic antiviral agents and further comprising 0.5 to 4 parts by mass of a surfactant, per 100 parts by mass of a polyolefin resin.
2. The extruded polyolefin resin foam according to claim 1, further comprising, in addition to the inorganic antiviral agent, an antioxidant in an amount of 0.05 to 1 part by mass per 100 parts by mass of the polyolefin resin.
3. The polyolefin-based extruded resin foam according to claim 1 or 2, characterized in that the sliced surface of the polyolefin-based extruded resin foam is either one of the following: a surface skin layer is removed, the center of the polyolefin-based extruded resin foam in the thickness direction is sliced straight, or the center of the polyolefin-based extruded resin foam in the thickness direction is profiled.
4. The polyolefin-based extruded resin foam according to any one of claims 1 to 3, characterized in that another polyolefin-based extruded resin foam is attached and laminated to the opposite surface of the sliced surface of the polyolefin-based extruded resin foam.
5. The polyolefin extruded resin foam according to any one of claims 1 to 4, characterized in that the base resin of the polyolefin extruded resin foam is made of any one of low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, very low-density polyethylene, polypropylene, polybutene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, and polypropylene, or a mixture of two or more of these blended together.
6. The polyolefin-based extruded resin foam according to any one of claims 1 to 5, characterized in that the polyolefin-based extruded resin foam has an uneven pattern formed on its surface.
7. The extruded polyolefin resin foam according to any one of claims 1 to 6, characterized in that the extruded polyolefin resin foam is used as a mat for an evacuation shelter.
8. A method for producing an extruded polyolefin resin foam containing an inorganic antiviral agent, comprising the steps of: The inorganic antiviral agent contained in the polyolefin-based extruded resin foam is any one of: (1) zirconium phosphate carrying silver or a silver compound by ion exchange; (2) a phosphate compound having a hydroxyapatite composition containing calcium and zinc carrying silver or silver ions by ion exchange; (3) zeolite carrying silver or copper by ion exchange; or (4) silver-carrying montmorillonite, The composition contains 1 to 8 parts by mass of at least one of the inorganic antiviral agents in total, and further contains 0.5 to 4 parts by mass of a surfactant, relative to 100 parts by mass of a polyolefin resin, The method for producing a polyolefin extruded resin foam containing the inorganic antiviral agent is foamed at a predetermined expansion ratio, and then the foam layer in the vicinity of the surface layer is cut to expose openings where the cell walls of the foam layer are opened, or the foam layer is cut at the center in the thickness direction of the polyolefin extruded resin foam or at a position offset by a predetermined distance from the center in the thickness direction to open the cell walls of the foam layer, thereby producing a slicing or profiling process, characterized in that the foam has a cell structure with an expansion ratio of 20 to 40 times and a closed cell structure with an average cell diameter of 200 to 1,500 μm.
9. The method for producing a polyolefin-based extruded resin foam according to claim 8, further comprising shaping the resin foam by further slicing at least a portion of the surface that has been sliced or profiled.
10. 10. The method for producing a polyolefin-based extruded resin foam according to claim 8 or 9, wherein another polyolefin-based extruded resin foam is attached and laminated to a surface opposite to the sliced surface of the polyolefin-based extruded resin foam.
Citation Information
Patent Citations
Medical PP inorganic antibacterial composite and preparation method thereof
CN104387669A
Antimicrobial thermoplastic resin foam
JP1995173318A
Antibacterial foaming resin particle and molded product made of the same
JP1999335481A
Formed thermoplastic resin and its manufacturing method
JP2001270958A
Method for preparing composite foam
JP2002001829A
